Acute effects of resisted and assisted locomotor activation on sprint performance - Matusinski, A.; Golas, A.; Zajac, A.; Maszczyk, A. (Biology of Sport, 2022)
Sprinting speed is one of the most significant motor abilities in team sport games and all sprint, hurdling and jumping events in athletics. Over the years numerous methods and devices have been developed to improve sprinting performance. One of the most effective methods of developing sprinting speed includes resisted sprinting with the use of different towing devices, parachutes, uphill running, and now intelligent drag technology. Resisted sprinting can be used for chronic changes in performance or for acute enhancement of running speed through locomotor post-activation. The other method of enhancing sprinting speed includes assisted sprinting in which the objective is to achieve supramaximal speed through high speed treadmill running, downhill sprinting, the use of elastic tubing or different towing mechanisms. The main objectives of this research were to determine the acute effects of resisted and assisted sprint activation on sprinting performance in male and female sprinters. Eleven, international and national level 200-400 m sprinters, 6 female and 5 male, participated in the study. The study protocol had a crossover design, with the activation protocol for both days consisting of either 3 × 30 m resisted sprints or 3 × 40 m assisted sprints. At baseline, and following the activation protocol, all athletes performed a 50 m maximum sprint, measured electronically with photocells from a crouched start. During particular trials, the SPRINT 1080 engine assisted measuring system was used with the load set individually to 10% BM. During the resisted and assisted PAP intervention the results of intragroup ANOVA revealed significant differences between resisted baseline results and resisted post activation results in the 10 m and 50 m test trials in men (respectively p = 0.002, ?2 = 0.25; p = 0.001, ?2 = 0.45), as well as in the group of female sprinters at these distances (10 m and 50 m) (respectively p = 0.002, ?2 = 0.20; p = 0.001, ?2 = 0.29). There were no statistically significant improvements in the 10 and 50 m test trials following assisted activation for both female and male sprinters. It was concluded that resisted sprint activation with a load of 10% BM enhances sprinting speed over 50 m in elite male and female sprinters.